Meat and milk self-sufficiency in Asia: Forecast trends and implications - Rutherford, A.S. (Wiley, 1999)
Recent structural changes in dietary patterns in Asia resulting from economic development are placing increasing pressure on the existing production systems in the region - particularly those systems producing ruminant meat, non-ruminant meat and milk. This has significant policy implications for the countries in the region in terms of self-sufficiency goals in these commodities and the associated inter- and intra-regional trade opportunities in the future. Forecasts of ruminant meat, non-ruminant meat and milk production and consumption for selected Asian countries between the years 2000 and 2010 revealed the following: China, Pakistan and Viet Nam are likely to be self-sufficient with respect to ruminant meat; Malaysia is likely to continue to be a net importer of ruminant meat; India and Malaysia will be more than self-sufficient with respect to non-ruminant meat with the converse being true for Pakistan; and India, Laos and Pakistan will be self-sufficient with respect to milk production with the possibility of Indonesia, Thailand and Cambodia becoming self-sufficient if the current trends continue. Structural changes in the early 1980s generally resulted in higher average annual growth rates of production - particularly is non-ruminant meat production. thus forecasts of ruminant meat production and consumption by 2000 using the medium-term average annual growth rates for production present a more favourable outcome in terms of self-sufficiency for countries such as Bangladesh, the Philippines and Viet Nam but a less favourable outcome for countries such as Indonesia, Malaysia, Laos and India. Similar forecasts for non-ruminant meat indicated an improvement in the long-term non-ruminant self-sufficiency estimates for most cases-particularly for Bangladesh, China and Cambodia. Intensification and commercialisation of meat production systems have increased meat self-sufficiency in a number of countries but often at the expense of grain self-sufficiency. Given these trends, the impact of trade liberalisation measures on livestock production in the region and inter- and intra-regional trade of livestock commodities and grain is likely to be significant.